DEVELOPMENT OF INDONESIAN SPEECH RECOGNITION SYSTEM BASED ON DEEP NEURAL NETWORK FOR GIVING SUBTITLES ON RECORDED NEWS BROADCAST - Alghifari, Mochamad
developed to improve accessibility for hearing-impaired news viewers. To create a speech recognition system for the news broadcast domain, a speech corpus, text corpus, and appropriate acoustic modeling techniques are needed. This final project discusses the construction of the speech corpus and text corpus in the news broadcast domain as well as the construction of acoustic models, language models, and lexicon which are then integrated into the speech recognition system.